Multilingual learners, linguistic pluralism and implications for education and research - Chalmers, H; Murphy, V (Routledge, 2021)
In this chapter, the authors address issues concerning multilingual pupils in linguistically diverse classrooms. Taking Britain as an example, they begin with a very brief history lesson which demonstrates that this country has long been, and continues to be, a multilingual society. The authors share concerns over the terminology used to denote multilingual pupils in the UK and turn their attention to whether and to what extent a multilingual pedagogy does/could have benefits to pupils. They discuss the theoretical background which justifies the need for this research, and present relevant past research that has attempted to examine the impact of multilingual approaches. The authors conclude by arguing that while what has been done is of significant value in our efforts to understand and articulate best practice for multilingual pupils, they need more and more experimental, research to establish causal links between practice and outcomes in linguistically diverse classrooms.